Labium superius oris mucormycosis: an enigma - Varasala, Praveena; Mallineni, Ujjwala (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Mucormycosis is an aggressive opportunistic fungal infection affecting immunocompromised patients. It has six manifestations: rhinocerebral, pulmonary, cutaneous, gastrointestinal, disseminated and localized infection. However, isolated mucormycosis of upper lip (labium superius oris) without any bony invasion has not been reported in literature to the best of our knowledge. Hence this poses a diagnostic challenge. A 50-year-old male came with left sided nasal pain and left sided nasal obstruction associated with very mild uniform swelling of upper lip of 24 months duration. He underwent FESS in a local hospital and was misdiagnosed as granulomatous origin probably Tuberculosis. Even on ATT the symptoms didn’t subside and hence presented to our hospital. On incisional biopsy deep fungal infection probably mucor was reported and he was put on tab Posaconazole 300 mg OD. On recurrent upper lip swelling, excision biopsy was done. HPE was reported as fibrocollagenous stroma interspersed by multiple non-caseating epitheloid granulomas with plenty of foreign body type of giant cells. PAS showed broad aseptate acute angled hyphal forms suggestive of mucor. The follow up clinical presentation of the patient was very satisfactory with complete regression of upper lip swelling and no damage to surrounding structures. The case report highlights the existence of localized form of mucormycosis without bony necrosis in immunocompetent patients which require minimal surgical intervention along with oral medical therapy rather than extensive debridement.